Brucellosis with nephrotic syndrome, nephritis and IgA nephropathy. Issue 804 (October 1992) - Siegelmann, N.; Abraham, A. S.; Rudensky, B.; Shemesh, O.
Abstract : A patient with systemic brucellosis due to Brucella melitensis had severe renal involvement. Clinical features included hypertension, macroscopic haematuria, massive proteinuria of 10 g per 24 hours and azotaemia. Following treatment with antibiotics, the azotaemia resolved and proteinuria decreased to less than 0.5 g per 24 hours, but microscopic haematuria and hypertension persisted. Renal biopsy during recovery revealed IgA nephropathy with minimal mesangial changes, suggesting a causal relation between brucellosis and IgA nephropathy with a reversible nephrotic syndrome.